PENGARUH LOKASI DAN KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING PADA ANGKRINGAN AROMA KOPI PANCUR PRAJEKAN BONDOWOSO - Hidayat, Irwan; Soeliha, Siti; Ediyanto, Ediyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Marketing management is a science that studies the implementation of marketing. In marketing management science, companies can determine which market to target by fostering good relationships with the target market. The purpose of this study was to analyze and examine the effect of location and service quality in determining consumer loyalty with purchasing decisions as an intervening variable. The population in this study are employees of Angkringan Aroma Kopi Pancur Prajekan Bondowoso. The sampling method was determined by simple random sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that location has a significant positive effect on purchasing decisions, service quality has a significant positive effect on purchasing decisions, location has a significant positive effect on consumer loyalty, service quality has a significant positive effect on consumer loyalty, purchase decisions have a significant positive effect on consumer loyalty. significantly positive on consumer loyalty. The results of the indirect influence hypothesis show that the location variable on consumer loyalty through purchasing decisions has a significant positive effect, and service quality on consumer loyalty through purchasing decisions has a positive but not significant effect.